Local two-group bubble size model for adiabatic air–water flow in a large diameter pipe using CFD code - Jinyeong Bak; Manh Long Doan; Seongbae Park; Jae Jun Jeong; Byongjo Yun (Case Studies in Thermal Engineering)
Accurate prediction of bubble behavior in large diameter pipes is crucial for evaluating the performance of safety systems, steam generators, and heat exchangers in nuclear systems. Bubble behavior in large diameter pipes under two-phase flow significantly differs from that in small pipes. With the increasing use of computational fluid dynamics (CFD) codes, predicting interfacial area concentration (IAC) is critical for understanding multi-dimensional bubble behavior. This study developed a two-group local bubble size model for bubbly, slug, and churn flows under adiabatic conditions. The model includes correlations for void fraction and bubble sizes of two groups, which were implemented into CFD codes and validated against experimental data from large diameter pipes with low-pressure air–water flow. Results show the model's prediction accuracy surpasses existing correlations. The developed correlations are applicable across a range of flow conditions covering pipe diameters in the range 0.05–0.152 m, pressures from atmospheric to 300 kPa, superficial liquid velocities from 0.25 m/s to 2.85 m/s, and superficial gas velocities from 0.04 m/s to 5.48 m/s. The model is expected to enhance the prediction capabilities of CFD codes for the adiabatic two-group two-phase flows in the large diameter pipes.